Backgrounds of violence in young people - Bouabdallah KACEMI (Social Sciences Journal, 1970)
The problem of violence and youth are frequently in the public or private space of ,could notwithout days or weeks without to read or hear or see the multiple forms of violence in urban areas andthrough the media fluid. This makes us to raise several questions about this phenomenon and practicesamong young people to know what is behind her motives and mechanism which give rise to have thedesire to exercise violence in urban areas.The revival of the city of Oran sample are similar to thosepractices that assume to us the seriousness of the situation if not every one of us according to hiscompetence, in turn, to understand the real motives of the backgrounds and the reasons that makethese young people a taste of social ills.